Modern ophthalmic optics - Alonso, José 1965-; Gómez-Pedrero, José A. 1971-; Quiroga, Juan A. (Cambridge University Press, 2019)
"This book is a comprehensive account of the most recent developments in modern ophthalmic optics. It makes use of the powerful matrix formalism to describe curvature and power, providing a unified view of the optical and geometrical properties of lenses. This unified approach is applicable to the design and properties of not only spectacle lenses, but also contact and intraocular lenses (IOL). The newest developments in lens design, manufacturing and testing are discussed, with an emphasis on the description of free-form technology, which has surpassed traditional manufacturing methods and allows digital lenses to be specifically designed with the unique requirements of the user. Other important topics which are covered include modern lens materials, up-to-date lens measuring techniques, contact and intraocular lenses, progressive power lenses, low vision aids, ocular protection and coatings. Providing a broad overview of recent developments in the field, it is ideal for researchers, manufacturers and practitioners involved in ophthalmic optics"--
Keywords: Ophthalmic lenses; Ophthalmology; Eyeglasses; SCIENCE / Optics; Electronic books